2020
DOI: 10.22271/chemi.2020.v8.i4ac.10013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different growing condition and sowing time on fenugreek: A review

Abstract: Fenugreek needed to grow at correct time for higher growth and in protected structure for increase yield. The aim of protected cultivation is to attain independence of climate and weather. During this study we tend to examine the literature of various protected structure like shade net of various colour like white, black, red, blue, green and polyhouse of low cost, medium cost and high cost conjointly examine sowing time on September, October, November, December. Result show that planted throughout November so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Results from the experiment showed that the maximum weight of individual pod (119.99 mg) was recorded from the S 2 (15 November) treatment where the minimum weight of individual pod (106.42 mg) was revealed from the S 3 (30 November) treatment. A similar result was observed by [15]. Different phosphorus levels significantly influence the weight of individual pods during the experimentation (Table 6).…”
Section: Weight Of Individual Pod (Mg)supporting
confidence: 85%
“…Results from the experiment showed that the maximum weight of individual pod (119.99 mg) was recorded from the S 2 (15 November) treatment where the minimum weight of individual pod (106.42 mg) was revealed from the S 3 (30 November) treatment. A similar result was observed by [15]. Different phosphorus levels significantly influence the weight of individual pods during the experimentation (Table 6).…”
Section: Weight Of Individual Pod (Mg)supporting
confidence: 85%